Project-based learning model to promote students critical and creative thinking skills - Salsadella Andini; Rusmini Rusmini (Jurnal Pijar Mipa, 2022)
This study aimed  to assess the worthiness of the project-based learning model in training critical and creative thinking skills on colloidal material. This research is a pre-experimental design with a one group pretest-posttest design. 31 students of XI MIPA 4 at MAN 1 Mojokerto were the targets studied in this study. The results of this study are: 1) The average percentage of the project-based learning treatment obtained is 78% in the good category (1st meeting) and 88% in the very good category (2nd meeting). 2) The activity of students is declared good with a percentage of 88%. 3) Critical and creative thinking skills have high criteria, as shown in the results of N-Gain 0.70, 0.73, and 0.73. 4) Student learning outcomes increase, which indicated from one complete student to 28 complete students. 5) A total of 95% positive responses were obtained from 31 students on the Project-Based Learning model. So the conclusion that can be drawn is that the project based learning model can train students' critical and creative thinking skills on colloidal material. project based learning model can be used as an alternative learning strategy to practice critical and creative thinking skills as the demands of 21st-century skills. It is more maximal and meaningful so that the desired learning activities and better results study can be achieved.